The silver tsunami and rural small business retention: What can communities do?. Issue 2 (15th March 2017) - Templin, Elizabeth; Chazdon, Scott; Muske, Glenn; Barroso, Felipe Dyna; Osborne, Lillian; Craig, William
Abstract: Since many rural communities have a disproportionately older population, the "silver tsunami" of retiring baby boomers has fueled interest in small business succession as a business retention strategy. Most business succession research has focused solely on the firm level without addressing community-level aspects. This article emphasizes the importance of community responses by blending findings from a rural small business survey with key informant interviews. Study findings suggest that successful business succession creates an opportunity for business expansion. Of the 118 new owners surveyed, 41% increased employment, 68% increased sales volume, and 68% increased their customer base. Communities reported facilitating business succession by (1) emphasizing the importance of succession planning, (2) reducing financial, time, and confidentiality barriers, and (3) providing accessible resources.